Application of Cooperative Script Learning Mode through Listening Story Method in Improving Listening Ability of Class V : Penerapan Model Pembelajaran Cooperative Script Melalui Metode Simak Cerita dalam Kemampuan Menyimak Siswa di Sekolah Dasar Kelas V - Nadya, Try Jihan; Liansari, Vevy (Indonesian Journal of Education Methods Development, 2023)
The background of this research was to find out whether the Cooperative Script learning model experienced an improvement if it was applied to Indonesian language learning in the story listening skills of fifth grade students. a story. One of the efforts to improve students' listening skills is to apply the Cooperative Script learning model that uses discussion-based learning and the teacher is only a facilitator. This study uses a descriptive qualitative research design. The subjects of this study were all fifth grade students of Madrasah Ibtidaiyah Darussalam. Data collection techniques used in this study were observation, interviews and documentation. Data analysis uses data presentation and conclusion drawing. The results of this study indicate that the ability of students to listen to stories through the Cooperative Script method can be improved as seen in the activity and student learning outcomes. So this method is very effective to apply.